PENGARUH REWARD TERHADAP MOTIVASI BELAJAR SISWA: (Studi Survei di SMP Negeri 114 Jakarta Utara) - Salima, Qolbun; Maria Ulfah; Najwa Hania Zahro; Firdaus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning motivation of some students at SMP Negeri 114 North Jakarta, which was suspected to be influenced by the teacher's provision of reward during the learning process. Preliminary observation found that several students were less active, less confident in asking questions, and less enthusiastic in completing assignments. This study aimed to determine the effect of reward on students' learning motivation. A quantitative approach with a survey method was used. The population consisted of 881 students, with a sample of 90 students determined using the Slovin formula and proportionate stratified random sampling technique. Data were collected through questionnaires, observation, interviews, and documentation, and were analyzed using validity and reliability tests, prerequisite tests, and the Pearson Product Moment correlation test. The results showed a positive and significant effect of reward on students' learning motivation, with a Pearson correlation coefficient (r) of 0.461 and a significance value of 0.000 (< 0.05), indicating a moderate relationship. The coefficient of determination (R Square) of 0.212 indicates that reward contributes 21.2% to students' learning motivation, while the remaining 78.8% is influenced by other factors. Therefore, the Alternative Hypothesis (Ha) was accepted and the Null Hypothesis (H0) was rejected, meaning that the better the reward given, the higher the students' learning motivation.